Natural colorant and methods thereof. - Syed Muhammad, Sharifah Kharidah; Amin, Hossein; Bakar, Jamilah (2010)

(untitled)
To provide a material composed mainly of a material derived from dragon fruit having to provide a supplement, a drug, a cosmetic or a food produced by using the material. The invention provide a material derived from dragon fruit, especially, a powder of dragon fruit, and a supplement, a drug, a cosmetic or a food containing the above material as a component.